2018
DOI: 10.1002/jaba.513
|View full text |Cite
|
Sign up to set email alerts
|

Does the Good Behavior Game evoke negative peer pressure? Analyses in primary and secondary classrooms

Abstract: The Good Behavior Game (GBG) is a classroom management system that employs an interdependent group contingency, whereby students work as a team to win the game. Although previous anecdotal data have suggested that this arrangement may promote prosocial behavior, teachers may have concerns about its fairness and potential to evoke negative peer interactions (especially toward students who break the rules). We evaluated disruptive behaviors and social interactions during the GBG in a secondary classroom for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
3
46
2
Order By: Relevance
“…Because the GBG is typically an interdependent group contingency in which the behavior of all team members affects reinforcer delivery, peer‐mediated contingencies likely contribute to its effectiveness. Groves and Austin () found that the GBG evoked appropriate peer interaction and support. However, more research is needed to examine how the GBG affects peer interactions and whether changes in peer interactions could elucidate mechanisms responsible for long‐term behavioral improvements following the GBG (Groves & Austin, ), including reduced drug use and risky sexual behavior in adulthood (Kellam et al, ).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Because the GBG is typically an interdependent group contingency in which the behavior of all team members affects reinforcer delivery, peer‐mediated contingencies likely contribute to its effectiveness. Groves and Austin () found that the GBG evoked appropriate peer interaction and support. However, more research is needed to examine how the GBG affects peer interactions and whether changes in peer interactions could elucidate mechanisms responsible for long‐term behavioral improvements following the GBG (Groves & Austin, ), including reduced drug use and risky sexual behavior in adulthood (Kellam et al, ).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The best efforts at classroom management, as well as simulation games, can contribute to reduction in student disruptive behavior (Murphy, & Van Brunt, 2018;Floress, Rock, & Hailemariam, 2017). The behavior-specific praise of students, high-probability request sequence, precorrection activity, active supervision, instructional choice, and teaching feedback, as well as good behavior game, can be resulted in a decreased number of student disruptive behaviors (Freeman, 2018: Groves, & Austin, 2019Rubow, Vollmer, & Joslyn, 2018). The positive teacher behaviors, as well as professional development, produced significant improvements in reductions in disruptive behavior (Cook et al, 2018;Bradshaw et al, 2018).…”
Section: Disruptive Behaviorsmentioning
confidence: 99%
“…Groves and Austin () noted, in their social validty measure, that secondary students positively responded to an interdependet group contingency (i.e., Good Behavior Game). In their study, the authors focused on earning or losing points based on group behavior.…”
Section: Discussionmentioning
confidence: 99%
“…An important additional direction for future researchers would be to include measures of task engagement, as measured through systematic observation and permanent product, when phones are allowed versus when they are not allowed in classrooms, to evaluate whether the students' reported increase in focus positively affects educational objectives. In addition, future researchers should develop and evaluate procedures for reducing unapproved usage (e.g., texting, social media) while simultaneously increasing approved usage (e.g., active responding through live polling) and consider evaluating the acceptability of this intervention with students and the teachers implementing it (Groves & Austin, ).…”
Section: Discussionmentioning
confidence: 99%